PENERJEMAHAN KETERAMPILAN BERBAHASA YANG BERHUBUNGAN DENGAN PROSES PENGEMBANGAN BAHASA SEBUAH TAWARAN KEWIRAUSAHAAN DALAM KEGIATAN BERBAHASA - Ingrid Veronica Kusumawardani (Jurnal Ilmiah Publipreneur, 2018)
This  journal  contains  argumentation  of  researcher’s  idea  on  language  skill  which not  only  have  an  influence  to  language  development  but  also  entrepreneur’s activity which can be executed by any person who wants to be a translator. Considering that translation is a language activity having opportunity to produce income  for  translator.  Researcher  intensively  executes  the  research  towards translation process with literature review and data analysis to gain validated data that  can  be  accounted  for  because  it  is  done  in  accordance  with  carefull  and detailed observation.  Researcher used descriptive methodology. In implementation, researcher used literature review  for  the  data  used  resourcing  from  literature  data,  then  the  data  analysis  of  this journal is qualitative analysis that is analysis of contain to data. Therefore the data was analyzed based on the level of its linkage to the problem.  As  for  the  discussion  of  this  journal  contains  exposure  on  basis  of  researcher’s understanding  to  some  theories  which  researcher  is  as  actor  of  language  and entrepreneur in the field of language. In the discussion, researcher explained what needed skills are by a translator, how the relationship between translation and language development, then  how big the ability  of  translation  can  be  used  as  one  of  language  activities  which can  produce income through the language activity. Therefore in the end of discussion shall be delivered all goals of this journal. Next, in  conclusion  and  suggestion  part,  researcher  would  deliver  the  observation  and discussion, then followed by suggestion in line with the conlucion